Improving the general physical fitness of children 7-9 years old in sports acrobatics - Demyanova L.M. ,; Agafonov S.V. ,; Chub S.A. ,; Kaznacheev V.V. ,; Sigida V.P. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to improve the general physical training of children 7-9 years old in sports acrobatics. Methods and structure of the study. The experiment took place in the municipal budgetary institution of additional education in Rostov-on-Don “Sports School No. 6”. The participants in the experiment were 12 acrobats aged 7-9 years, 6 of whom were included in the experimental group and 6 athletes in the control group. Scientific research methods included: pedagogical observation, pedagogical testing, pedagogical experiment, methods of mathematical statistics. Results and conclusions. The results of the conducted pedagogical experiment clearly demonstrated the effectiveness of the developed sets of physical exercises in sports acrobatics, aimed at improving the general physical training of young acrobats aged 7-9 years. Therefore, it can be argued that supplementing the content of general physical training programs in sports acrobatics for this age group with experimental complexes of physical exercises will significantly increase their level of physical and functional readiness.